2011
DOI: 10.1615/intjmedmushr.v13.i1.100
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Preservation, Regeneration, and Cultivation of Paecilomyces tenuipes (Peck) Samson (Ascomycetes), an Entomopathogenic Fungus Inoculated into the Silkworm Larva of Bombyx mori

Abstract: Paecilomyces tenuipes reportedly have anticancer and immune activities, along with various other medicinal uses. Cultured products with P. tenuipes are certified for use in food in South Korea, and processed goods containing this fungus have been developed in many countries, particularly South Korea, Japan, and China. Research on mass production technology-procured raw materials for the manufacture of P. tenuipes is very important; however, cultures of the fungus have been unstable. This study identified stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Paecilomyces tenuipes has been considered to be a valuable source of medicinal remedies and health promotion. (27,28). The immune-stimulating and antifatigue activities of Paecilomyces tenuipes have been investigated in animal models (14,29).…”
Section: Discussionmentioning
confidence: 99%
“…Paecilomyces tenuipes has been considered to be a valuable source of medicinal remedies and health promotion. (27,28). The immune-stimulating and antifatigue activities of Paecilomyces tenuipes have been investigated in animal models (14,29).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicated that many natural products which were extracted from fungi can be used in treating and preventing human diseases [21]. P. tenuipes is one of the most popular fungi in Asian nations, and is reported as valuable source of medicinal bioactive substances [22]. Our previous studies have shown that P. tenuipes M98 had high active ingredient content and safety.…”
Section: Discussionmentioning
confidence: 98%
“…In spite of lots of reports on the beneficial activities of Paecilomyces species, there have also been several studies on the toxicities of Paecilomyces species, especially P. sinclairii, including acute oral toxicity studies in dogs, subchronic oral toxicity study in rats and a series of genotoxicity studies (Ahn et al, 2003(Ahn et al, , 2004aJeong et al, 2012Jeong et al, , 2013. Among Paecilomyces species, the P. tenuipes-contained processed goods have also been developed in many countries, particularly South Korea (Nam et al, 2011). In order to identify the toxicity of the P. tenuipes, we performed the genotoxicity, acute and subchronic oral toxicity studies in rats.…”
Section: Discussionmentioning
confidence: 99%
“…These previous findings suggest the need for further studies to identify whether the P. tenuipes extract includes lysinoalanine and the renal toxicity of the P. tenuipes extract is species-specific. Since cultured products with the P. tenuipes, which have anticancer and immune activities, are certified for use in food in South Korea (Nam et al, 2011), it is important to provide accurate information on the safety concern of P. tenuipes to be developed as functional foods and nutritious medicines. Therefore, based on our current results, we suggest that further study is necessary to find no observed adverse effects level associated with karyomegaly using the P. tenuipes extract doses less than 500 mg/ kg and to confirm the P. tenuipes-related renal toxicity in other species.…”
Section: Discussionmentioning
confidence: 99%